Phosphate-deprivation and damage signalling by extracellular ATP - Matthus, Elsa; Ning, Youzheng; Shafiq, Fahad; Davies, Julia M. (Frontiers in Plant Science, 2023)
Phosphate deprivation compromises plant productivity and modulates immunity. DAMP signalling by extracellular ATP (eATP) could be compromised under phosphate deprivation by the lowered production of cytosolic ATP and the need to salvage eATP as a nutritional phosphate source. Phosphate-starved roots of Arabidopsis can still sense eATP, indicating robustness in receptor function. However, the resultant cytosolic free Ca2+ signature is impaired, indicating modulation of downstream components. This perspective on DAMP signalling by extracellular ATP (eATP) addresses the salvage of eATP under phosphate deprivation and its promotion of immunity, how Ca2+ signals are generated and how the Ca2+ signalling pathway could be overcome to allow beneficial fungal root colonization to fulfill phosphate demands. Safe passage for an endophytic fungus allowing root colonization could be achieved by its down-regulation of the Ca2+ channels that act downstream of the eATP receptors and by also preventing ROS accumulation, thus further impairing DAMP signalling.